Using a Warm Hand-Off Approach to Enroll African American Caregivers in a Multi-Site Clinical Trial: The Handshake Protocol. (January 2022) - Epps, Fayron; Brewster, Glenna; Phillips, Judy S.; Nash, Rachel; Shah, Raj C.; Hepburn, Kenneth
"Testing Tele-Savvy" was a three-arm randomized controlled trial that recruited participants from four National Institute on Aging (NIA)–funded Alzheimer's Disease Centers with Emory University serving as the coordinating center. The enrollment process involved each center providing a list of eligible caregivers to the coordinating center to consent. Initially, the site proposed to recruit primarily African American caregivers generated a significant amount of referrals to the coordinating center, but a gap occurred in translating them into enrolled participants. To increase the enrollment rate, a "Handshake Protocol" was established, which included a warm handoff approach. During preset phone calls each week, the research site coordinator introduced potential participants to a culturally congruent co-investigator from the coordinating center who then completed the consent process. Within the first month of implementation, the team was 97% effective in meeting its goals. This protocol is an example of a successful, innovative approach to enrolling minority participants in multi-site clinical trials.